Beauvoir and Western Thought from Plato to Butler - Mussett, Shannon M.; Wilkerson, William S., 1968- (Book collections on Project MUSE., 2012)
This book is a collection of essays on Beauvoir's influences, contemporary engagements, and legacy in the philosophical tradition. Despite a deep familiarity with the philosophical tradition and despite the groundbreaking influence of her own work, Simone de Beauvoir never embraced the idea of herself as a philosopher. Her legacy is similarly complicated. She is acclaimed as a revolutionary thinker on issues of gender, age, and oppression, but although much has been written weighing the influence she and Jean-Paul Sartre had on one another, the extent and sophistication of her engagement with the Western tradition broadly goes mostly unnoticed. This volume turns the spotlight on exactly that, examining Beauvoir's dialogue with her influences and contemporaries, as well as her impact on later thinkers - concluding with an autobiographical essay by bell hooks discussing the influence of Beauvoir's philosophy and life on her own work and career. These innovative essays both broaden our understanding of Beauvoir and suggest new ways of understanding canonical figures through the lens of her work.